Analysis of educated unemployment in Indonesia 2015-2024 - Musdalifah Musdalifah; Kalvin A. Parinding; Laendatu Paembonan; Yunus Sading; Rita Yunus (Privietlab, 2026)
This study examines the effects of the Provincial Minimum Wage or Upah Minimum Provinsi (UMP), Gross Regional Domestic Product (GRDP), and Mean Years of Schooling (MYS) on educated unemployment across Indonesian provinces from 2015 to 2024. Panel data from all 34 provinces were analyzed using panel data regressions. The simultaneous test confirms that all three variables significantly influence educated unemployment, with an R-squared value of 0.9732, indicating strong explanatory power. Partially, the minimum wage shows a negative and significant effect, consistent with efficiency wage theory, suggesting that wage increases are associated with greater labor market participation among educated workers. GRDP shows a positive and significant effect, consistent with a jobless growth pattern in which economic expansion is driven largely by capital-intensive sectors that absorb limited amounts of educated labor. Similarly, MYS positively and significantly affects educated unemployment, consistent with structural educational mismatch and over-education, where rising educational attainment outpaces the growth of qualified job opportunities, a condition associated with educated workers remaining voluntarily unemployed rather than accepting mismatched positions. By covering all 34 provinces over a full decade, this study extends prior, more geographically limited research and shows that provincial economic growth and rising educational attainment can coincide with, rather than reduce, the educated unemployment. These findings highlight the multidimensional nature of educated unemployment in Indonesia, requiring integrated policy responses, including aligning educational curricula with labor market demands, promoting labor-intensive and inclusive economic growth, and sustaining evidence-based minimum-wage policies across regions.